Prevalence of Burnout Syndrome among Physical Therapy House Officers: Burnout Syndrome Among House Officers - Noor, Kinza; Bibi, Saliha; Abbasi, Rimsha Razzaq; Azam, Muhammad Farooq; Bibi, Salma (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2024)
Burnout syndrome is a psychological syndrome that is caused by inter-personnel stressors related to prolonged and hectic working hours in a hospital setting. It is overwhelming exhaustion feelings of cynicism, detachment from the job, and lack of accomplishment. Objective: To find the prevalence of burnout syndrome in physical therapy house officers working in the hospitals of Rawalpindi and Islamabad. Methods: The selection of participants was done by the purposive method of sampling and data collection from the 161 included participants was done by using the Maslach Burnout Inventory-Human Services Survey. The analysis of data were done by using IBM Statistics SPSS version 22.0. Results: The means and standard deviation for the three components of burnout were found to be 25.09 ± 9.56 for Emotional Exhaustion (EE), 10.093 ± 5.93 for Depersonalization (DP), and 31.248 ± 9.45 for Personal Accomplishment (PA). The mean values fall in the range of moderate level for Emotional Exhaustion (EE), moderate level for Depersonalization (DP), and low level for Personal Accomplishment (PA). Overall, an average of moderate to high levels of burnout was found in the included participants. Conclusions: It is concluded that physical therapists working in Rawalpindi and Islamabad are at high risk of developing burnout because of hectic routines and because of the reason that they are not being paid for their work